Personality Development in Psychoanalytic Perspective: Literature Review - Sartika; Arlin Adam; Syamsu A. Kamaruddin; Ansyaruddin (Universitas Muhammadiyah Palu, 2024)
Psychoanalytic theory seeks to explain how personality develops with a focus on motivation, emotions, and other internal aspects. Essentially, psychoanalysis is the result of Freud's ideas about the power of preconscious structures (id, ego, and superego) in controlling human behavior. The implication is that human behavior is controlled by preconscious structures, manifested as imitations, with their control lying in lost childhood memories. The method used in this writing is a literature review, involving a critical analysis of written sources (literature) on a specific topic, enabling the creation of summaries, classifications, comparisons, or even evaluations. Freud believed that humans are constantly driven by a desire for pleasure. However, what one encounters in the external world may not always be an ideal condition that supports these drives. Hence, the idea of a conflict between these drives and the external world arises. This notion led Freud to the concept most famous among his others: the three points of human personality as the Ego (Latin for